Flavonoid Stability of Avocado Leaf (Persea americana Mill.) Extract on pH and Temperature Treatment - Kemit, Nico; Permana, Mayun; Diah Kencana, Pande Ketut (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 6 No 1 (2019): Scientific Journal of Food Technology (March), 2020)
This research aimed to get the etanol’s consentration and ratio avocado leaf to solvents on highest flavonoid content and antioxidant activity of avocado leaf extract and also get stability of pH and temperature for flavonoid extract avocado leaf. This research did into two step. First step was effect of etanol’s consentration and ratio avocado leaf to solvents. The experimental design used in this research was a completely randomized design with replication, which consisted of two factors. The first factor was etanol’s concentration (90 and 96%). The second factor was ratio avocado leaf to solvents (1:6, 1:8, 1:10). Data were analyzed with analysis of variance, followed by Duncan test. The best treatment on first step would use into second step of this reseach. Second step was effect of flavonoid content’s stability of extract avocado leaf to pH and temperature. The experimental design used in this research was a completely randomized design with replication, which consisted of two factors. The first factor was pH (4, 6 and 8). The second factor was temperature (70, 80 and 90OC). Data were analyzed with analysis of variance, followed by Duncan test. The results showed that the best treatment in first step was etanol 90% and ratio avocado leaf to solvent 1:6 which the highest resulted rendemen, total fenol, total flavonoid and antioxidant activity were 17.54%, 79.19 mg/g extrak, 69.19 mg/g extrak and 72.91%. The results showed that the best treatment second step was pH 4 and temperature 70OC which the best resulted total fenol, total flavonoid and antioxidant activity that stablest. Persentase that still stay at extract were 94.9%, 86.99% dan 85.08%.